The Effect of Emotional Attachment And Perceived Product Quality On Customer Loyalty With Customer Satisfaction As A Mediator - Muhammad Affidianto Arrusda; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This study aims to determine and examine the influence of emotional attachment and perceived product quality on customer loyalty with customer satisfaction as a mediator. This study uses a quantitative method. The sampling technique used is nonprobability sampling, specifically purposive sampling, with a sample size of 112 respondents. Data collection was conducted using a questionnaire distributed via Google Forms to respondents who had purchased Ventela products at least once. Data analysis techniques used in this study included data quality testing, classical assumption testing, multiple linear regression, and Sobel testing. The results of the study indicate that (1) emotional attachment has a positive and significant effect on customer satisfaction, (2) perceived product quality has a positive and significant effect on customer satisfaction, (3) emotional attachment has a positive and significant effect on customer loyalty, (4) perceived product quality has a positive and significant effect on customer loyalty, and (5) customer satisfaction does not affect customer loyalty.